Energy transfer via exciton transport in quantum dot based self-assembled fractal structures - Bernardo, César (2014)
Semiconductor quantum dot (QD) assemblies are promising systems for light harvesting and energy conversion and transfer, as they have a superior photostability compared to classical dyes and their absorption and emission properties can be tuned during synthesis. Here, we investigate excitonic energy transfer in self-assembled dentrite-type fractal structures consisting of QDs by microscopically mapping their fluorescence spectra and lifetimes. The behaviors of CdSe/ZnS and CdTe QD assemblies are compared; in particular, the energy transfer probability is found to be stronger in CdTebased structures, scaling with their radiation quantum yield. Our results indicate Förster-type energy transfer in both systems, although with a higher efficiency in CdTe. The energy transfer is caused by near-field (nonradiative) dipole−dipole coupling between the individual QDs within a dendrite, with the excitation migrating from the edges to the center of the structure. The experimental findings are supported by theoretical modeling results obtained by using master equations for exciton migration/decay kinetics in diffusion-limited fractal aggregates composed of identical particles.